Opportunities for UAV mapping to support unplanned settlement upgrading - Gevaert, C.M. (2020)
The effort to improve sub-standard living conditions in unplanned settlements is often hindered due to a lack of adequate spatial information describing the baseline situation and changes occurring during and after the upgrading process. Low-cost Unmanned Aerial Vehicles (UAVs) could provide very detailed, up-to-date spatial information for small unplanned areas as and when required. To investigate the utility of such platforms in settlement upgrading, UAV flights were conducted over approximately 150 ha of unplanned settlements in the City of Kigali in May and June 2015. Data obtained with UAV were supplemented by an analysis of the spatial information needs of various stakeholders involved in the upgrading project. In the context of the upgrading project, the results of this study identify four main benefits of using UAV imagery. First, it could replace the 2008 25 cm ortho-imagery by up-to-date 3 cm imagery in current workflows for map updating. Second, it enables the extraction of additional information which was previously unavailable, such as detailed elevation data to support surface water runoff analysis and drainage capacity calculations. Third, it speeds up field work and fourth, the imagery provides a foundation for communication between different stakeholders. When using UAVs it is also important to take many practical considerations into account, as well as the societal and ethical context. Results of the first experiences in Kigali indicate that while the use of UAV is not generally perceived as a problem by the local population, fear of forced displacement and expropriation may raise concerns amongst the residents. Communication between the UAV operator, the local government, local leaders and with the residents before and during flights, and sharing the benefits of the acquired information are important to mitigate these fear.